"There are no days off, just days without shows": precarious mobilities in the touring music industry. Issue 2 (4th May 2021) - Zendel, Adam
ABSTRACT: The proliferation of online streaming music has led to a loss of income from the sale of recorded music pressuring artists and technicians to find alternate avenues to earn income, particularly through touring. Yet, there is little study on the lives and experiences of workers who tour. I use Lefebvre's rhythmanalysis to analyze how the rhythm of "tour life" exposes workers to vulnerability and risk. Touring requires synchronizing the needs of daily life to an extreme form of employment-related geographical mobility. On tour, artists and workers struggle with basic self-care, eating, and sleeping in the context of constant travel. The rhythm of touring forces workers to be "always on" and always away in architectures that blur living and working space. The tour bus is a liminal space – neither home or worksite – yet features elements of both. Cultural work further produces an arrhythmic arrangement through the absorption of work into leisure time. For the public, travel or attending concerts are a form of leisure, the eurythmic counterpoint to their daily routines. For musicians and crew these are the quotidian elements of work. Working in the live music industry is seasonal, contractual and contingent on numerous cultural and economic forces. While touring music workers are an extreme case of employment related mobility, the rhythms of their working lives offer insight into the risk and vulnerability experienced by an increasingly mobile workforce.